2020
DOI: 10.1007/s10151-020-02148-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of sacral neuromodulation for chronic pelvic pain: a Finnish national multicenter study

Abstract: Background The aim of this study was to report the outcomes of sacral neuromodulation (SNM) in chronic pelvic pain (CPP) patients in the Finnish national cohort. Methods This was a register-based retrospective study, involving all the centers that provide SNM treatment in Finland. The data of all patients treated with SNM for CPP were gathered from Oulu-, Turku-, Tampere-and Helsinki University Hospitals, as well as Jyväskylä and Seinäjoki Central Hospitals. All patients who had been tested for SNM implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
(26 reference statements)
2
12
0
Order By: Relevance
“…The WMD in pain score on a 10‐point scale after SNM was −4.64 (95% CI = −5.32 to −3.95, p < 0.00001) (Figure 2). Six studies were excluded from quantitative analysis as they did not report mean ± SD VAS 14,21,26,28–30 . Three of these studies reported a significant decrease in pain score after SNM ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WMD in pain score on a 10‐point scale after SNM was −4.64 (95% CI = −5.32 to −3.95, p < 0.00001) (Figure 2). Six studies were excluded from quantitative analysis as they did not report mean ± SD VAS 14,21,26,28–30 . Three of these studies reported a significant decrease in pain score after SNM ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were excluded from quantitative analysis as they did not report mean ± SD VAS. 14,21,26,[28][29][30] Three of these studies reported a significant decrease in pain score after SNM (p < 0.05). The remaining three reported a decrease in pain score but did not perform statistical analysis (Supporting Information: Appendix).…”
Section: Primary Outcomementioning
confidence: 97%
“…The exact mechanism of action of SNM is unknown, however, it is believed to correct the balance between the peripheral sacral nerves and the central nervous system by stimulating the afferent sensory fibers of the pelvic and pudendal nerves [18]. Following its approval, SNM has been increasingly utilized for OAB, and the evidence base for its medium to long-term (3 plus years) safety and efficacy is gradually building up [19][20][21][22][23][24][25][26]. However, the majority of the existing literature has been funded by the SNM device manufacturer [21,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Based on evidence, the sacral portion of the spinal cord is the ideal site for neuromodulation in the treatment of CPP caused by different etiologies (19,22,23). CPP encompasses a number of treatment-resistant conditions including irritable bowel syndrome, interstitial cystitis, pudendal neuralgia, and coccygodynia (24).…”
Section: Discussionmentioning
confidence: 99%
“…Sacral neuromodulation (SNM) is one approach that has conventionally been used to manage overactive bladder, nonobstructive urinary retention, and fecal incontinence (25). SNM and SCS have shown success in the treatment of CPP (19,22,23,(26)(27)(28)(29)(30). Zabihi et al (29) reported positive results from SNM via a retrograde approach over S2-S4 for the treatment of refractory CPP, interstitial cystitis, and painful bladder pain syndrome.…”
Section: Discussionmentioning
confidence: 99%